Metabolism of F18, a Derivative of Calanolide A, in Human Liver Microsomes and Cytosol - Wu, Xiangmeng; Zhang, Qinghao; Guo, Jiamei; Jia, Yufei; Zhang, Ziqian; Zhao, Manman; Yang, Yakun; Wang, Baolian; Hu, Jinping; Sheng, Li; Li, Yan (Frontiers in Pharmacology, 2017)
10-Chloromethyl-11-demethyl-12-oxo-calanolide (F18), an analogue of calanolide A, is a novel potent nonnucleoside reverse transcriptase inhibitor against HIV-1. Here, we report the metabolic profile and the results of associated biochemical studies of F18 in vitro and in vivo. The metabolites of F18 were identified based on liquid chromatography-electrospray ionization mass spectrometry and/or nuclear magnetic resonance. Twenty-three metabolites of F18 were observed in liver microsomes in vitro. The metabolism of F18 involved 4-propyl chain oxidation, 10-chloromethyl oxidative dechlorination and 12-carbonyl reduction. Three metabolites (M1, M3-1 and M3-2) were also found in rat blood after oral administration of F18 and the reduction metabolites M3-1 and M3-2 were found to exhibit high potency for the inhibition of HIV-1 in vitro. The oxidative metabolism of F18 was mainly catalyzed by cytochrome P450 3A4 in human microsomes, whereas flavin-containing monooxygenases and 11β-hydroxysteroid dehydrogenase were found to be involved in its carbonyl reduction. In human cytosol, multiple carbonyl reductases, including aldo-keto reductase 1C, short-chain dehydrogenases/reductases and quinone oxidoreductase 1, were demonstrated to be responsible for F18 carbonyl reduction. In conclusion, the in vitro metabolism of F18 involves multiple drug metabolizing enzymes, and several metabolites exhibited anti-HIV-1 activities. Notably, the described results provide the first demonstration of the capability of FMOs for carbonyl reduction.